For the following system, use the second equation to make a substitution for y in the first equation.

3x + y = 1
y + 4 = 5x

What is the resulting equation?

3x + 5x - 4 = 1
3x + 4 - 5x = 1
3x + 5x + 4 = 1

Respuesta :

CPED

Answer:

Option A: 3x + 5x - 4 = 1

Step-by-step explanation:

Given that:

3x + y = 1  ------------- eq1

y + 4 = 5x ------------ eq2

Now for substitution in eq1 we will get a value of y from eq2:

y = 5x - 4

Substituting in eq1 we get:

3x + 5x - 4 = 1

i hope it will help you!

Answer:

3x + 5x - 4 = 1

Step-by-step explanation: